Red Tide Events and Seasonal Variations in the Partial Pressure of CO2 and Related Parameters in Shellfish-Farming Bays, Southeastern Coast of Korea - Shim, JeongHee; Ye, Mi-Ju; Lim, Jae-Hyun; Kwon, Jung-No; Kim, Jeong Bae (Frontiers in Marine Science, 2021)
Mixed results have been reported on the evaluation of the coastal carbon cycle and its contribution to the global carbon cycle, mainly due to the shortage of observational data and the considerable spatiotemporal variability arising from complex biogeochemical factors. In this study, the partial pressure of carbon dioxide (pCO2) and related environmental factors were measured in the Jinhae–Geoje–Tongyeong areas of the southeastern Korean Peninsula in February 2014, August 2014, April 2015, and October 2015. The mean pCO2 of surface seawater ranged from 215 µatm to 471 µatm and exhibited a high correlation with the surface seawater temperature when data for August were excluded (R2 = 0.69), indicating that the seasonal variation in CO2 could be largely attributed to the variation in seawater temperature. However, a severe red tide event occurred in August 2014, when the lowest pCO2 value was observed despite a relatively high seawater temperature. It is considered that the active biological production of phytoplankton related to red tides counteracted the summer increase in pCO2. Based on the correlation between pCO2 and temperature, the estimated decrease in pCO2 caused by non-thermal factors was approximately 200 µatm. During the entire study period, the air–sea CO2 flux ranged from -14.2 mmol m-2 d-1 to 3.7 mmol m-2 d-1, indicating that the study area served as an overall sink for atmospheric CO2. The mean annual CO2 flux estimated from the correlation with temperature was -5.1 mmol m-2 d-1. However, because this estimate did not include reductions caused by sporadic events of biological production, such as red tides and phytoplankton blooms, the actual uptake flux is considered to be higher. The mean saturation state (ΩAr) value of carbonate aragonite was 2.61 for surface water and 2.04 for bottom water. However, the mean ΩAr of bottom water was <2 in August and October, and the ΩAr values measured at some of the bottom water stations in August were <1. Considering that the period from August to October corresponds to the fertilization and growth stages of shellfish, such low ΩAr values could be very damaging to shellfish production and the aquaculture industry.